Does Work-Time Flexibility Really Improve the Reconciliation of Family and Work? - Juliane Scheffel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Temporal work flexibility is often viewed as means to improve the reconciliation of family and work. By exploiting theGerman re-unification and the particularities of the labor market of the German Democratic Republic, I show that flexitime allows mothers to spend more time with their children. The additional childcare time is added to the already existing work burden. It is accommodated by reductions in regenerative time and leisure which makes a reconciliation of family and work even more strenuous. A comparison between East andWest suggests a significantly positive endogeneity bias that largely overstates the effectiveness of work-time flexibility on parental time.
Keywords: J08; J13; J22; 330